К археологической карте памятников VIII – первой половины X вв. южной части Керченского полуострова - Пономарев, Л.Ю. (Боспорские исследования, 2011)
В статье обобщены материалы к археологической карте памятников VIII – первой половины X вв. южной части Керченского полуострова. В статті узагальнено матеріали до археологічної карти пам’ятників VIII- першої половини Х ст. південної частини Керченського півострова. Materials to the archaeological map of the monument of the southern part of the Kerch Peninsula dated from the 8th – the first half of the 10th cc. are summarized in the article.